2011
DOI: 10.1093/ndt/gfr092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lowering dialysate sodium on flow-mediated dilatation in patients with chronic kidney disease

Abstract: Reducing dialysate sodium concentration reduced ED, and provided better control of IDWG and BP, but increased dialysis-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The disruption of BP homeostasis can be reflected by elevated BPV and may be due to the impairment of endothelial or cardiovascular function, or decreased compliance of elastic arteries that stem from arterial stiffness. In line with this finding, a study that lowered dialysate sodium concentration from 143 to 137 mmol/L did improve endothelial dysfunction as measured by flow‐mediated dilatation in HD patients . Our previous study, using a similar sodium gradient with the present study, showed that arterial stiffness, assessed by aortic pulse wave velocity, and LVH were improved at the end of 1‐year dialysate sodium concentration lowering .…”
Section: Discussionsupporting
confidence: 91%
“…The disruption of BP homeostasis can be reflected by elevated BPV and may be due to the impairment of endothelial or cardiovascular function, or decreased compliance of elastic arteries that stem from arterial stiffness. In line with this finding, a study that lowered dialysate sodium concentration from 143 to 137 mmol/L did improve endothelial dysfunction as measured by flow‐mediated dilatation in HD patients . Our previous study, using a similar sodium gradient with the present study, showed that arterial stiffness, assessed by aortic pulse wave velocity, and LVH were improved at the end of 1‐year dialysate sodium concentration lowering .…”
Section: Discussionsupporting
confidence: 91%
“…Mechanistically, the high sodium gradient might increase blood pressure by increasing body fluid volume during the session but might also have a more complex basis (eg, endothelial dysfunction) as suggested earlier . It is also important to acknowledge that there are, as with many areas of investigation, several contrary studies that found no blood pressure lowering effect of low DNa …”
Section: Clinical Effects Of Dialysis Sodium Concentrationmentioning
confidence: 91%
“…Again, some studies observed that choosing a lower dialysate sodium (134 to <140 mEq/L) was associated with more episodes of intradialytic hypotension and cramps and longer time to recover post‐dialysis, whereas many other studies have reported no significant differences in intradialytic events …”
Section: Introductionmentioning
confidence: 99%